STRATEGI PEMASARAN DAN ETIKA BISNIS PADA PENJUALAN KOSMETIK SECARA ONLINE MENURUT ISLAM (STUDI KASUS PADA PELAKU BISNIS DI ERA PANDEMI COVID-19) - Roni, La Ode (Pusat Studi Ekonomi, Publikasi Ilmiah dan Pengembangan SDM, 2022)
now entered the digital realm, where sellers and buyers can do marketing online, in line with the progress of the times and the Covid-19 outbreak. However, certain parties often ignore Islamic business standards because of the ease of doing internet marketing. This poses a relative danger to the development and growth of the company. Applying Islamic business principles is very important for those who are in the business world. Because business people must follow Islamic business ethics, namely moral principles based on the Qur'an and Hadith. The following problem formulation includes the following questions, which this research tries to answer: What were the conditions for cosmetics that could be sold before and during the Covid-19 pandemic? What internet marketing techniques for halal cosmetic products are used by business people during the Covid-19 pandemic, and how are they implemented? Online marketing approach based on Islamic business ethics. This study uses a case study approach and a descriptive qualitative research design to examine cosmetics sellers. Data collection techniques using the results of observation, interviews, and documentation. The results of this study indicate that cosmetic vendors have incorporated Islamic business ethics into their online marketing strategy for halal cosmetic products, namely by adhering to the principle of unity, which prohibits prohibitions against workers and customers based on SARA, by providing clear product descriptions. by being responsible and trustworthy, by engaging in fair competition, and by never pressuring customers to make a purchase